Indigenous Sports of India: Connecting Past to the Present - Dr. Milankumar Bhatt (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Games are very popular throughout the world and everyone i.e. right from the children to adults prefers to participate in them. Various traditional games are part and parcel of Indian tradition. When we discuss about India, it has always exhibited its rich culture and tradition. Whereas, games have been an important part of Indian culture endlessly right from their origin. India is considered as a place of origin for a number of traditional games which are well-known throughout the world in present time. All these games require technical and tactical skills along-with other physiological components like speed, strength, stamina, agility and coordinative abilities. Apart from this our traditional games require very little equipment and they are less expensive in comparison to the modern games, and as a result traditional games of Indian origin became more popular amongst the masses. Yet much needs to be done at the govt. level so that they can be well promoted and Indians can retain their glorious heritage.